(In)Justiça de segurança nacional: a criminalização do comunismo no Brasil entre 1935-1945 - Bisi, Adriana de Oliveira Gonzaga (2016)
The purpose of this thesis is to investigate, from a critical-criminological perspective, the political-ideological functions performed by the repressive system for political crimes, valid in Brazil during the years from 1935 to 1945, specifically by the National Security Law and the National Security Court. It is based on the hypothesis of research that the repressive system of political crimes was part of a broader mechanism of social control, decisive to deal politically with the “order demands”, especially: the consolidation of a nationalist-authoritarian political project; the development of industrial capitalism; the protection of the system of private ownership of the means of production and of the corporate organization of labor relations; political domestication of the urban working class, in the sense of neutralizing its political organization and its empowerment. Several types of knowledge were articulated in the legal form to build the legitimating discourses of the need to establish a legislation and a court of exception, which operated with an authoritarian legal-political logic whose center of meaning was the relativization or suppression of individual rights and political freedoms, and the elimination of political dissent, in order to protect the political and social order of the Brazilian Nation from its political enemies, notably: the Communists (declared function). In this sense, Science (Sociology, Positivist Criminology and Positivist Social Psychology, Political Theory, Constitutional Theory), the Catholic Church, the Press, and Literature, have built and reinforced specific social representations of the ideas and political struggles of the working class. They were generically labeled “communists”, bringing together all the stereotypes that this sign contains: enemies, traitors, hateful, violent, barbarians, diabolical, dangerous, sneaky, promiscuous, mob, criminals, thus justifying tough vigilance and criminal repression. Using a historical-dialectical methodological perspective, the aim was to reveal the unsaid side of these discourses (undeclared functions) and, for that, we tried to insert the processes of criminalization of “political crimes” in the context of the peculiar socialhistorical Brazilian capitalism and the concrete class struggles of the period. Thus, it is evident that, in this dynamic, there was a criminalization not only of people or acts but, above all, of certain political ideas: those revolutionary forms of thinking of the working class.